United Nations' Intergovernmental Panel on Climate Change's (IPCC) Special Report on Climate Change and Land (SRCCL) - Chapter 2: Land-Climate Interactions (2019)
Land and climate interact in complex ways through changes in forcing and multiple biophysical and biogeochemical feedbacks across different spatial and temporal scales. This chapter assesses climate impacts on land and land impacts on climate, the human contributions to these changes, as well as land-based adaptation and mitigation response options to combat projected climate changes